Labview™ for Nutra-Biostrip in Herbal Quality Assessment - Mohd Noor, Ahmad; Yap, Maxsim Mee Sim; Mohd Kamal, Mohamed; Ramly, Nil; Ali Yeon, Md Shakaff; Chang, Chew-Cheen (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my